2019
DOI: 10.1016/j.scr.2019.101528
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological exposures may precipitate craniosynostosis through targeted stem cell depletion

Abstract: The Centers for Disease Control and Prevention, National Birth Defects Study suggests that environmental exposures including maternal thyroid diseases, maternal nicotine use, and use of selective serotonin reuptake inhibitors (SSRIs) may exacerbate incidence and or severity of craniofacial abnormalities including craniosynostosis. Premature fusion of a suture(s) of the skull defines the birth defect craniosynostosis which occurs in 1:1800–2500 births. A proposed mechanism of craniosynostosis is the disruption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Craniosynostosis has a prevalence of 1:1,800-2,500 births, being associated to some genetic mutations (Cdc45, Twist, Fgfr, and Tcf12) and/or environmental factors including nicotine, hyperthyroidism in pregnant women, and importantly, the use of antidepressants (Twigg and Wilkie, 2015;Durham et al, 2017). The relationship between these environmental factors and craniosynostosis has been described in animal models, which show an altered proliferation and differentiation of stem/progenitor cells, and in humans, in which the newborns from mothers exposed to these disturbances have an increase in craniosynostosis prevalence (Shuey et al, 1992;Carmichael et al, 2008;Grewal et al, 2008;Browne et al, 2011;Berard et al, 2015Berard et al, , 2017Durham et al, 2017Durham et al, , 2019; Figure 1B).…”
Section: Craniofacial Development and The Origin Of Craniofacial Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Craniosynostosis has a prevalence of 1:1,800-2,500 births, being associated to some genetic mutations (Cdc45, Twist, Fgfr, and Tcf12) and/or environmental factors including nicotine, hyperthyroidism in pregnant women, and importantly, the use of antidepressants (Twigg and Wilkie, 2015;Durham et al, 2017). The relationship between these environmental factors and craniosynostosis has been described in animal models, which show an altered proliferation and differentiation of stem/progenitor cells, and in humans, in which the newborns from mothers exposed to these disturbances have an increase in craniosynostosis prevalence (Shuey et al, 1992;Carmichael et al, 2008;Grewal et al, 2008;Browne et al, 2011;Berard et al, 2015Berard et al, , 2017Durham et al, 2017Durham et al, , 2019; Figure 1B).…”
Section: Craniofacial Development and The Origin Of Craniofacial Defectsmentioning
confidence: 99%
“…As the abovementioned effects of maternal depression at birth, negative effects of the use of antidepressants during pregnancy have been reported, including non-optimal birth outcomes (i.e., preterm delivery and lower Apgar scores), persistent pulmonary hypertension of the newborn, neonatal withdrawal/toxicity syndrome, greater internalizing behaviors at toddler age, and greater risk for autism spectrum disorder ( Meltzer-Brody et al, 2011 ; Huybrechts et al, 2015 ; Field, 2017b ). Regarding the craniofacial region, the use of SSRI has also been associated with bone defects like craniosynostosis and dental malformations, affecting mainly the proliferation and differentiation equilibrium in progenitor cells, as described in different experimental models ( Shuey et al, 1992 ; Moiseiwitsch et al, 1998 ; Cray et al, 2014 ; Calibuso-Salazar and Ten Eyck, 2015 ; Durham et al, 2019 ), and associated with an increased risk of craniofacial malformations in humans ( Alwan et al, 2007 ; Berard et al, 2015 , 2017 ; Reefhuis et al, 2015 ; Gao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The suture mesenchyme represents a unique skeletogenic stem cell niche in the developing skull, serving as a transient reservoir of mesenchymal stromal cells (MSC) and osteoprogenitors (see Figure 1) [21,22]. Regardless of the initial trigger underlying CS etiology, it is believed that in these disorders the calvarial suture stem cell niche undergoes an accelerated exhaustion, which ultimately drives the premature ossification of the suture mesenchyme [20,23]. Therefore, strategies to maintain and/or replenish the stem cell reservoir, either through direct cell transplantation, or through paracrine stimulation of endogenous cells, would be highly desirable.…”
Section: Craniosynostosis: a Heterogeneous Conditionmentioning
confidence: 99%
“…Premature closure of the suture could lead to craniosynostosis. Studies have demonstrated a unique stem cell niche in cranial sutures, where multiple populations ofSeveral subpopulations of suture mesenchymal stem cells (SuSCs) were identified, including Gli1-positive (Gli1 + ) cells, Axin2-expressing (Axin2 + ) cells, and postnatal Prx1expressing (Prx1 + ) cells [46][47][48][49]. All these cells possess the ability for self-renewal and continually produce skeletal cell descendants.…”
Section: Suturesmentioning
confidence: 99%